IMF Staff papers, Volume 45 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1998)
This paper analyzes some leading indicators of currency crises, and proposes a specific early warning system. This system involves monitoring the evolution of several indicators that tend to exhibit an unusual behavior in the periods preceding a crisis. When an indicator exceeds a certain threshold value, this is interpreted as a warning 'signal' that a currency crisis may take place. The variables that have the best track record within this approach include exports, deviations of the real exchange rate from trend, and the ratio of broad money to gross international reserves, output, and equity prices.